Chiral separation of new designer drugs (Cathinones) on chiral ion-exchange type stationary phases - Wolrab, Denise; Frühauf, Peter; Moulisová, Alena; Kuchař, Martin; Gerner, Christopher; Lindner, Wolfgang; Kohout, Michal (Journal of pharmaceutical and biomedical analysis, 2016)
We present the enantioseparation of new designer drugs from the cathinone family on structurally different chiral ion-exchange type stationary phases. A novel strong cation-exchange type chiral stationary phase was synthesized and its performance compared with previously reported ion-exchange type chiral stationary phases. The influence of structural elements of the chiral selectors on their chromatographic performance was studied and the possibilities of tuning chromatographic parameters by varying the polarity of the employed mobile phases were determined. Evidence is provided that a change in mobile phase composition strongly influences the solvation shell of the polarized and polarizable units of the selectors and analytes, as well as ionizable mobile phase additives. Furthermore, the structural features of the selectors (e.g. the size of aromatic units and their substitution pattern) are shown to play a key role in the effective formation of diastereomeric complexes with analytes. Thus, we have achieved the enantioseparation of all test analytes with a mass spectrometry-compatible mobile phase with a chiral strong cation-exchange type stationary phase.
Keywords: Cathinones; kationtoměniče; Stereoisomerism; Enantiomer separation; chromatografie iontoměničová; stereoizomerie; Chiral ion exchanger; Chiral stationary phase; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; Alkaloids; alkaloidy; Cation Exchange Resins; nové syntetické drogy; Chromatography, Ion Exchange; New designer drugs; Designer Drugs